2022
DOI: 10.3390/children9101506
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Plasma Pro-Inflammatory Cytokine Levels in Children with Refractory Epilepsies

Abstract: Paediatric epilepsy is a multifaceted neurological disorder with various aetiologies. Up to 30% of patients are considered drug-resistant. The background impact of interfering inflammatory and neuronal pathways has been closely linked to paediatric epilepsy. The characteristics of the inflamed state have been described not only in epilepsies, which are considered prototypes of an inflammatory pathophysiology, but also in patients with drug-resistant epilepsy, especially in epileptic encephalopathies. The imbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 74 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…In several studies of our review [36,41,42,52,53] some chemokines have been found to be increased. The one that has been identified in the largest number of studies is CCL2, a potent chemoattractant protein for monocytes, and hence is alternatively referred to as monocyte chemoattractant protein-1 (MCP-1).…”
Section: Chemokinesmentioning
confidence: 75%
“…In several studies of our review [36,41,42,52,53] some chemokines have been found to be increased. The one that has been identified in the largest number of studies is CCL2, a potent chemoattractant protein for monocytes, and hence is alternatively referred to as monocyte chemoattractant protein-1 (MCP-1).…”
Section: Chemokinesmentioning
confidence: 75%
“…In several studies of our review [38,49,54,55,57], levels of some chemokines were found to be increased. The one that was identified in the largest number of studies was CCL2, a potent chemoattractant protein for monocytes, and hence is alternatively referred to as monocyte chemoattractant protein-1 (MCP-1).…”
Section: Chemokinesmentioning
confidence: 75%
“…[ 35 ] Thus, COX-2-coupled PGE2 release may induce seizures through epileptogenesis-related mechanisms. [ 36 37 ] Yasmen et al . [ 38 ] proved that administering small-molecule inhibitors of microsomal PGE synthase-1 blunts brain inflammation and is neuroprotective.…”
Section: Discussionmentioning
confidence: 99%